PERANAN GURU DALAM PEMBELAJARAN BAHASA - Sri Widayati (Universitas Muhammadiyah Kotabumi, 2019)
Teacher is a figure which the position is very important in education. Idealteacher always with their students in or out the class. Then, the teachers’ hearthalways reflected in daily life, not only as the symbol in the office. To be a goodteacher, someone must comprehend about all the materials, can make a goodplanning before teaching, have a good adaptation with the changing, alwaysimprove their ability, and know well about their students. The most important isthe teacher must have good sincere in teaching and learning proccess.